Enhancing the Competitiveness of Small and Medium Enterprises (SMEs) Through the Implementation of Sustainable Customer Relationship Management Strategies - Nenden Eva; Devi Veronica (Acceleration, Quantum, Information Technology and Algorithm Journal, 2025)
This study aims to analyze user satisfaction with ADINUSA e-learning services through the Customer Relationship Management (CRM) approach with the ADO (Antecedents, Decisions, Outcomes) framework. Data were obtained from user reviews and ratings, which showed that 86.5% of users were satisfied, while 13.5% indicated dissatisfaction. Thematic analysis identified six main issues that affect user satisfaction, namely material quality, assignments, system errors, language, mentoring, networks, and prices. The most dominant problems were related to materials, followed by technical constraints and the use of language that was less appropriate to the needs of novice users. The implementation of a structured and responsive CRM strategy has proven effective in increasing user satisfaction and loyalty. The concept of Sustainable CRM (SCRM) is also considered relevant in supporting the sustainability of digital learning services. These findings recommend the need to improve the quality of materials, technical improvements, and the presentation of more adaptive and sustainable services in order to maintain the platform's competitive advantage amidst the competition in the e-learning industry.